Characteristics and service use of NSW Quitline callers with and without mental health conditions - Lodge, Simone; Bartlem, Kate; Gibson, Lauren; Fehily, Caitlin; Bradley, Tegan; McKeon, Emma; Reakes, Kate; Rickards, Sandra; Hastings, Phillipa; Bowman, Jenny (Frontiers in Psychiatry, 2022)
Smoking rates remain higher for people with a mental health condition compared to the general population and contribute to greater chronic disease burden and premature mortality. Quitline services offer telephone-based smoking cessation support to the public and have been shown to be effective. There is limited research exploring the characteristics of smokers with a mental health condition who use the Quitline or the benefit they may gain from doing so. This observational study aimed to compare demographic and smoking related characteristics, service use and cessation attempts of callers to the New South Wales Quitline (2016-2018) with and without a mental health condition (N=4,219). At baseline, desire to quit smoking was similar for both groups, however participants with a mental health condition had higher nicotine dependency and had made more quit attempts prior to engaging with the service. During program enrolment, quit attempts and 24-hour smoke free periods were similar, however participants with a mental health condition engaged in a greater number of calls with Quitline compared to those without. The findings suggest Quitline efficacy for people with a mental health condition in making a quit attempt and abstaining from smoking for at least 24 hours. Increasing the use of Quitline services and understanding service use for this critical group of smokers will increase the likelihood that their quit attempts are transformed into sustained periods of smoking abstinence. Future research should explore whether tailoring of Quitline service provision for people with mental health conditions may increase the likelihood of quit success.